Culturally-Sensitive Factors in the Learning Environment of Science Classrooms in Brunei Darussalam - Dhinsda, H.; Fraser, Barry (Bentham Open, 2011)
The aims of this study were to validate the psychometric properties of the Cultural Learning Environment Questionnaire (CLEQ) when used in a new context, to evaluate cultural learning environment factors among lower secondary students, and to investigate gender and age differences in students’ perceptions on the CLEQ. The CLEQ includes the seven culturally-sensitive scales of Gender Equity, Collaboration, Deference, Competition, Teacher Authority, Modelling and Congruence. The sample consisted of 912 Grade 8 students (51% male; 49% female; mean age of 14.1 years) from coeducational schools in Brunei Darussalam. When data from administering the CLEQ were analysed, its factorial validity, alpha reliability, discriminant validity, and ability to differentiate between schools and classrooms were supported. Overall students perceived that both sexes were treated equally by moderately authoritarian teachers, that their classrooms were highly collaborative, competitive and modelled science and that science learning was associated with their out-of-school experiences. Students’ perceptions of classroom environment were not influenced by their age or sex. Needed research for improving cultural learning environments in science classes is recommended.